2020
DOI: 10.1007/s40264-020-00957-w
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factor Considerations in Statistical Signal Detection: Using Subgroup Disproportionality to Uncover Risk Groups for Adverse Drug Reactions in VigiBase

Abstract: Introduction In the treatment of the individual patient, a vision is to achieve the best possible balance between benefit and harm. Such tailored therapy relies upon the identification and characterisation of risk factors for adverse drug reactions. Information relevant to risk factor considerations can be captured in adverse event reports and could be utilised in statistical signal detection. Objective The aim of this study was to explore whether statistical screening of a broad range of risk factors within a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 18 publications
0
46
0
Order By: Relevance
“…By using a novel subgroup disproportionality approach [ 16 ], this study found that patient age was not a risk factor for adverse event reporting with ICIs as compared to other antineoplastic drugs. In VigiBase, there were not signals of disproportionate reporting with ICIs specifically detected in older patients (age ≥65 years) and not present in the disproportionality analysis over the entire dataset (i.e., regardless of patient age and with the inclusion of safety reports missing information on patient age).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…By using a novel subgroup disproportionality approach [ 16 ], this study found that patient age was not a risk factor for adverse event reporting with ICIs as compared to other antineoplastic drugs. In VigiBase, there were not signals of disproportionate reporting with ICIs specifically detected in older patients (age ≥65 years) and not present in the disproportionality analysis over the entire dataset (i.e., regardless of patient age and with the inclusion of safety reports missing information on patient age).…”
Section: Discussionmentioning
confidence: 99%
“…Disproportionality analysis is a valuable methodological approach well consolidated and extensively used in pharmacovigilance studies on databases of spontaneous reporting to characterize ICI toxicity [ 19 ]. Recently, Sandeberg et al [ 16 ], proposed subgroup disproportionality analyses to take into account the diversity that underlines safety reports of different patients, the confounding factors and the potential distortions of disproportionate measurements computed regardless of risk groups for ADRs. Indeed, subgroup disproportionality analysis benefits from both high sensitivity and precision over crude analyses in large databases [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research published by the WHO-Uppsala Monitoring Centre in fact supports our definition of the independent variable using concomitant drugs to infer a patient’s underlying diseases. The researchers considered concomitant diseases among the patient risk factors for ADRs reported in VigiBase, defined subgroups of such diseases using concomitant drug indications as proxies, and proposed subgroup disproportionality analysis as a statistical methodology for risk characterization in the ensuing patient subpopulations for ADR onset [ 34 ].…”
Section: Discussionmentioning
confidence: 99%